Echocardiographic predictors of cardiovascular morbidity and mortality in women from the general population. (30th August 2020) - Lundorff, Ingrid; Modin, Daniel; Mogelvang, Rasmus; Godsk Jørgensen, Peter; Schnohr, Peter; Gislason, Gunnar; Biering-Sørensen, Tor
Abstract: Aims: Global longitudinal strain (GLS) is a strong predictor of adverse cardiovascular outcome in men. However, studies have indicated that GLS may not predict cardiovascular outcomes as effectively in women. The aim of this study was to identify echocardiographic predictors of cardiovascular morbidity and mortality in women from the general population. Methods and results: A total of 1245 women from the general population free of heart failure (HF) and atrial fibrillation had an echocardiographic examination performed including tissue Doppler imaging. In this subset, 747 women had images eligible for strain analysis. Endpoint was a composite of acute myocardial infarction, HF, and cardiovascular death. During follow-up (median 12.5 years), 162 women (13.0%) reached the composite outcome. These women had higher left ventricular (LV) mass index (LVMI), more LV hypertrophy, lower E / A, higher E / e ′, larger LV dimensions, and longer deceleration time. LVMI and e ′ remained as significant predictors of the composite outcome [LVMI: hazard ratio (HR) 1.10, 95% confidence interval (CI) 1.03–1.17, P = 0.004, per 5 g/m 2 increase] ( e ′: HR 1.53, 95% CI 1.07–2.20, P = 0.020, per 1 cm/s decrease) after adjusting for age, hypertension, systolic blood pressure, diabetes mellitus, total cholesterol, smoking status, prevalent ischaemic heart disease, LV ejection fraction, E / e ′, E, E / A, interventricular septum thickness in diastole, left ventricular posterior wall in diastole, a ′, body surface area, and pro-brain natriuretic peptide. GLS was not an independent predictor of outcome after multivariable adjustment. Conclusion: The degree of LV hypertrophy assessed as LVMI and diastolic dysfunction evaluated by e ′ are associated with adverse cardiovascular outcome in women from the general population. Graphical Abstract: